Protective immunity provided by a new modified SERA protein peptide: Its immunogenetic characteristics and correlation with 3D structure (2012)
The serine repeat antigen (SERA) protein is a leading candidate molecule for inclusion as a component in a multi-antigen, multi-stage, minimal subunit-based, chemically synthesised anti-malarial vaccine. Peptides having high red blood cell binding affinity (known as HABPs) have been identified in this protein. The 6733 HABP was located in the C-terminal portion of the 47-kDa fragment while HABP 6754 was located in the C-terminal region of the 56-kDa fragment. These conserved HABPs failed to induce an immune response. Critical red blood cell binding residues and/or their neighbours (assessed by glycine-analogue scanning) were replaced by others having the same mass, volume and surface but different polarity, rendering some of them highly immunogenic when assessed by antibody production against the parasite or its proteins and protection-inducers against experimental challenge with a highly infectious Aotus monkey-adapted Plasmodium falciparum strain. This manuscript presents some modified HABPs as vaccine candidate components for enriching our tailor-made anti-malarial vaccine repertoire, as well as their 3D structure obtained by 1H-NMR displaying a short-structured region, differently from the native ones having random structures. © 2011 Springer-Verlag.